Intermediate-Energy Fragmentation of Heavy-Element Beams: A Novel Approach Towards the Nuclear Drip-Lines - Souliotis, G. A. (HNPS Advances in Nuclear Physics, 2019)
The fragmentation of heavy beams at intermediate energy and the opportunities offered by this in the exploration of heavy nuclei near the drip lines will be discussed. First, a study of 1 9 7Au projectile fragmentation at 30 MeV/nucleon will be presented in which an appreciable number of new p-rich nuclei were observed. Perspectives of proton radioactivity studies using the fragmentation approach will be discussed. Second, a study of the fission of 2 3 8U projectiles at 20 MeV/nucleon will be presented, where a number of new neutron rich nuclei were identified. Production rates of extremely η-rich nuclides from a typical projectile-fragmentation facility are given. A large number of nuclei along the astrophysical r-process path can be investigated and approach of the neutron dripline in the region Z=45-50 may be possible. The ability to produce and study these either p-rich or η-rich nuclei at intermediate (and possibly lower) energy facilities may open a variety of possibilities for experimental studies of exotic heavy nuclei.